2015
DOI: 10.1186/s12909-015-0352-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric patients’ perspectives of student involvement in their care

Abstract: BackgroundIn the education of professionals in psychiatry, one challenge is to provide clinical placements with opportunities for students to interact and have direct contact with patients. The aim of this study was to explore Swedish psychiatric patients’ perspectives on student participation in their care.MethodIn a cross-sectional survey design, 655 adult psychiatric patients at a university hospital completed questionnaires. These questionnaires included statements about student involvement, student gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 30 publications
5
29
1
Order By: Relevance
“…These attitudes served as incentives for older nurses in the mental health service to develop other possibilities of care, mainly focused on therapeutic relationship and communication. 18,19 This finding is consistent with the reality of Volta Redonda, in which the integration of teaching -university -and work (CAPS) was understood as beneficial for all those involved, since it required a practice consistent with the proposal of a CAPS and critical and reflective thinking for quality, non-fragmented Mental Health Care.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…These attitudes served as incentives for older nurses in the mental health service to develop other possibilities of care, mainly focused on therapeutic relationship and communication. 18,19 This finding is consistent with the reality of Volta Redonda, in which the integration of teaching -university -and work (CAPS) was understood as beneficial for all those involved, since it required a practice consistent with the proposal of a CAPS and critical and reflective thinking for quality, non-fragmented Mental Health Care.…”
Section: Discussionsupporting
confidence: 68%
“…18 It is worth highlighting that the student's approach to the new care model in mental health services was also seen as comfortable and positive according to a study carried out in Sweden. 19 In addition to this positive view, interdisciplinary exchange, through the multiprofessional team, is important for Teaching Nursing in Mental Health Martins GCS, Peres MAA, Santos TCF, Queirós PJP, Paiva CF, Almeida Filho AJ the teaching-learning process of students in mental health to provide quality care, in addition to being in line with the proposal of the DCN of 2001, mainly with the provision in its Article 14. 6,19 As far as stigmatization is concerned, a study conducted in the United States showed that the inclusion of students in services made the prejudice lessened and the availability for care free of pre-judgments increased.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations